Development of Boki Maruru Karst Landscape Area Geotrail in Supporting Geotourim Activites in Central Halmahera Regency - Abdul Kadir Dahlan Arif; Putri Citra M. Abidin; Adrian Nurdin Mantara (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
In order to enrich the existing tourism model in Central Halmahera Regency (Halteng), as an area that has geological, biological and cultural diversity, the development of the Boki Maruru karst landscape area geotrail is one solution. The presence of geotrail aims to foster public awareness in caring for and participating in maintaining the earth's heritage in the Boki Maruru Karst Natural landscape area as well as an added economic value for the community itself. In an effort to develop geotrail, it is important to map the geotrail path. This paper will discuss the mapping of geotrail sites using descriptive qualitative methods. Data collection is done by observation and literature study and then analyzed using SWOT. The results showed that there are three geotrail sites in the Boki Maruru Karst Natural Landscape Area, namely Telaga Yonello (Kawinet Peak), Batu Lubang Cave and Sageyen River Side. Based on the results of the SWOT analysis conducted, it is still necessary to improve supporting facilities such as visibility, increase human resources in geotrail management and geotourism guides to create a well-managed geotrail.